PEMBENTUKAN SAKOLA KARAJINAN RAKYAT CIPACING - Gunawan, Wahju; Humaedi, Sahadi (Prosiding Penelitian dan Pengabdian kepada Masyarakat, 2018)
ABSTRACTÂ The PPMP OKK activities entitled "The Establishment of Sakola Karajinan Rakyat in Cipacing" is located at RW 01 on Cipacing Village in Jatinangor, Sumedang. The purpose of its establishment is to overcome poverty in society if it is done in a sustainable and comprehensive manner. Besides that, it is able to regenerate the art of local peopleâs craft for the outsiders in a systematically, successfully, and appropriately.With the implementation of this kind of activity, it is hoped that people can see directly about the process of making their craft and at the same time they can share their knowledge with the craftsmen as well. The craftsmen themselves were hoping to teach their knowledge to the next generation, so that in the future they can maintain this craftâs culture and also pass it on to the next generation.The activities that have been done here are intended to introduce various of original crafts that comes from Cipacing in order to be able to compete to a wider market share, so it can help them to improve the economy as well, which so far their economies are still relatively low. Most of the craftsmen can sell their craft directly to consumers through the learning process that is carried out at an affordable price. Based on these activities, they are able to achieve a good profit.Â ABSTRAKÂ PPMP OKK ini berjudul âPembentukan Sakola Karajinan Rakyat Cipacingâ di RW 01 Desa Cipacing, Kec, Jatinangor, Kab, Sumedang. Adapun tujuan dari Sakola Karajinan Rakyat yang secara berkelanjutan dan menyeluruh dapat mengatasi kemiskinan di masyarakat serta dapat meregenasikan seni kerajinan masyarakat lokal ke masyarakat luar dengan sistematis dan berhasil guna serta tepat guna.Dengan adanya kegiatan âSakola Karajinan Rakyatâ ini diharapkan masyarakat bisa langsung datang melihat proses pembuatan kerajinan, dan berbagi ilmu dengan para pengrajin. Masyarakat pengrajin itu sendiri diharapkan mampu menjadi âguruâ atau mengajarkan ilmunya, sehingga dapat mempertahankan budaya dan mewariskannya kepada generasi selanjutnya.Kegiatan Sakola Karajinan Rakyat ini bertujuan untuk memperkenalkan kerajinan Cipacing ke mangsa pasar yang lebih luas, sehingga membantu mengangkat perekonomian para pengarajin yang selama ini masih tergolong rendah. Sehingga, mayoritas para pengrajin dapat menjual kerajinannya langsung kepada konsumen melalui proses pembelajaran di sakola tersebut dengan harga yang terjangkau konsumen, sehingga keuntungannya banyak diambil oleh para pengrajin.